2021
DOI: 10.2147/ijn.s318124
|View full text |Cite
|
Sign up to set email alerts
|

Farnesylthiosalicylic Acid-Loaded Albumin Nanoparticle Alleviates Renal Fibrosis by Inhibiting Ras/Raf1/p38 Signaling Pathway

Abstract: Background Renal fibrosis is the common pathway in chronic kidney diseases progression to end-stage renal disease, but to date, no clinical drug for its treatment is approved. It has been demonstrated that the inhibitor of proto-oncogene Ras, farnesylthiosalicylic acid (FTS), shows therapeutic potential for renal fibrosis, but its application was hindered by the water-insolubility and low bioavailability. Hence, in this study, we improved these properties of FTS by encapsulating it into bovine ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Chitosan NPs complexed with siRNA against an inflammatory enzyme required injection 3 d prior to UUO surgery ( 9 ). Albumin NPs loaded with small molecules that block p38 signaling entailed injection 2 d post-UUO surgery ( 63 ). This point is of clinical importance; as early development of CKD is asymptomatic, patients are mostly diagnosed at a later disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan NPs complexed with siRNA against an inflammatory enzyme required injection 3 d prior to UUO surgery ( 9 ). Albumin NPs loaded with small molecules that block p38 signaling entailed injection 2 d post-UUO surgery ( 63 ). This point is of clinical importance; as early development of CKD is asymptomatic, patients are mostly diagnosed at a later disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported that inhibiting the p38MAPK signaling pathway is beneficial to alleviate various kidney diseases [ 12 , 13 , 44 , 45 , 46 ]. Studies conducted on kidneys from hyperglycemic mice and HG-stimulated podocytes have shown that p38MAPK is involved in triggering chain reactions associated with hyperglycemia-induced nephrin endocytosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al encapsulated FTS in bovine serum albumin nanoparticles (AN-FTS) to improve its characteristics. Mouse experiments have demonstrated that AN-FTS preferentially accumulates in the fibrotic kidney, which can significantly reduce renal fibrosis and inflammation compared to free drugs ( 43 ).…”
Section: Nanoparticles and Renal Fibrosismentioning
confidence: 99%